MANAJEMEN PENDIDIKAN ISLAM: KONSEP PLANNING DITINJAU DALAM AYAT AL-QUR’AN - Ade, Putra (Universitas Islam Negeri (UIN) Sumatera Utara, 2022)
Planning is the initial stage in the implementation of management functions in an agency/organization, including educational institutions. The planning function really determines the achievement of targets and the early stages of measuring achievements. Al-Qur'an is a guideline for Muslims, in it teaches about how the whole concept of a plan. This study aims to analyze the concept of planning in terms of verses of the Qur'an. The method used is a descriptive-analytical study, through a qualitative approach. The data was obtained through observation and study of the verses of the Qur'an. Furthermore, it is analyzed using reduction techniques, data presentation, and drawing conclusions/verification. The results of the analysis were tested for validity through triangulation techniques. The results of this study indicate that in the Islamic management function, the role of planning is very important. Because planning is the first step or strategy taken to achieve the desired goal. Various planning concepts are described in the Qur'an so that they become a guide for mankind to carry out a plan to achieve the planned target or goal. There are at least 3 (three) verses studied in this study.